Strategi Pengembangan Pariwisata Halal di Kuta Mandalika Kabupaten Lombok Tengah - Abdul Basit (Tourism Scientific Journal, 2021)
This research seeks to find out how the policy direction of halal tourism development strategy in Kuta Mandalika Central Lombok Regency. The method used in this study is qualitative using a descriptive approach with swot strengthening in strategy determination. The results of the study showed the right strategies used are: developing halal tourism destination programs, floating halal tourism marketing programs to develop institutional or halal tourism governance and float halal tourism industry programs. Implementation of halal tourism development strategy policy direction in Kuta Mandalika based on SWOT such as: Explore the potential of natural and artificial tourism in the Kuta Mandalika Lombok area by structuring tourist attractions and empowering the community to develop artificial tourism in the Kuta Mandalika Lombok area such as developing business activities, culinary, crafts, and arts. Cooperate with halal certificate agency MUI and the Food and Drug Supervisory Agency (BPOM) to certify halal products to provide guarantees for Muslim tourists in enjoying tourism in the Kuta Mandalika lombok area. Promoting halal tourism through various social media and exhibitions both at the National and International levels continuously, by doing strong promotions to introduce tourist attractions in the Kuta Mandalika Lombok area, with a strong promotion carried out by the Tourism Office can increase the interest of tourists visiting the Kuta Mandalika Lombok area.